2007
DOI: 10.2460/javma.230.5.697
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic syndrome in dogs: 24 cases (1996–2005)

Abstract: Results indicated that hemophagocytic syndrome may occur more frequently in dogs than has previously been suspected on the basis of the paucity of reported cases. Although most dogs had definable underlying disease conditions, idiopathic hemophagocytic syndrome was also identified. Hemophagocytic syndrome of any cause is potentially life-threatening; however, the prognosis should be adjusted on the basis of the associated disease process and potential for successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(107 citation statements)
references
References 20 publications
5
98
0
4
Order By: Relevance
“…Acquired HPS has been reported in humans, rhesus macaques, rats, cats, and dogs (Weiss 2007;Stromberg et al 1983;Ide et al 2009;Cotroneo, Colby, and Bergin 2011). Causes of HPS, regardless of species, include infections, neoplasms, and altered immune function.…”
Section: Thrombocytopenia and Rbc Decreases Were Notmentioning
confidence: 99%
“…Acquired HPS has been reported in humans, rhesus macaques, rats, cats, and dogs (Weiss 2007;Stromberg et al 1983;Ide et al 2009;Cotroneo, Colby, and Bergin 2011). Causes of HPS, regardless of species, include infections, neoplasms, and altered immune function.…”
Section: Thrombocytopenia and Rbc Decreases Were Notmentioning
confidence: 99%
“…The disorder often occurs secondary to conditions associated with systemic macrophage activation (Larroche and Mouthon 2004, Weiss 2007, Schram and others 2016). Reactive HPS can be difficult to differentiate from haemophagocytic HS due to significant overlap in the clinical and pathological abnormalities commonly found in both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases in people and dogs are associated with conditions which promote systemic macrophage activation. A multi-institutional study of reactive HPS in people found 37 per cent of cases were secondary to neoplasia, 25 per cent due to an infectious agent and 21 per cent associated with an autoimmune disorder; a retrospective study in dogs reported a similar distribution of underlying diseases (Weiss 2007, Schram and others 2016). Serum cytokine profiles of people with HPS indicate these primary disease processes promote uncontrolled T lymphocyte activation (Larroche and Mouthon, 2004, Janka and Lehmberg 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations